THE BRIDGE INTERRELATION AND RAILWAY VEHICLE WITH SOME APPROACHES AND APPLICATIONS - Miheev, H. V.; Krugovova, E. A.; Kovalov, R. V. (Science and Transport Progress, 2010)
Some approaches and applications of railway vehicle and bridge interaction are presented. The results of computer simulation are considered.